Polη O-GlcNAcylation governs genome integrity during translesion DNA synthesis. Issue 1 (December 2017) - Ma, Xiaolu; Liu, Hongmei; Li, Jing; Wang, Yihao; Ding, Yue-He; Shen, Hongyan; Yang, Yeran; Sun, Chenyi; Huang, Min; Tu, Yingfeng; Liu, Yang; Zhao, Yongliang; et al.
Abstract DNA polymerase η (Polη) facilitates translesion DNA synthesis (TLS) across ultraviolet (UV) irradiation- and cisplatin-induced DNA lesions implicated in skin carcinogenesis and chemoresistant phenotype formation, respectively. However, whether post-translational modifications of Polη are involved in these processes remains largely unknown. Here, we reported that human Polη undergoes O-GlcNAcylation at threonine 457 by O-GlcNAc transferase upon DNA damage. Abrogation of this modification results in a reduced level of CRL4CDT2 -dependent Polη polyubiquitination at lysine 462, a delayed p97-dependent removal of Polη from replication forks, and significantly enhanced UV-induced mutagenesis even though Polη focus formation and its efficacy to bypass across cyclobutane pyrimidine dimers after UV irradiation are not affected. Furthermore, the O-GlcNAc-deficient T457A mutation impairs TLS to bypass across cisplatin-induced lesions, causing increased cellular sensitivity to cisplatin. Our findings demonstrate a novel role of Polη O-GlcNAcylation in TLS regulation and genome stability maintenance and establish a new rationale to improve chemotherapeutic treatment. Polη is a key player in translesion DNA synthesis. Here, the authors uncover that, in response to DNA damage, Polη undergoes O-GlcNAcylation at threonine 457 by O-GlcNAc transferase to facilitate the timely disassembly of Polη after DNA lesion bypass.